Status and influencing factors of elder neglect by geriatric nursing assistants in Chinese nursing homes: a cross-sectional survey - Wang, Jing; Yang, Zhihua; Li, Ya; Ma, Ruijuan; Zhang, Liping; Du, Yage; Dou, Haoying (Frontiers in Medicine, 2023)
Background In nursing homes, elder neglect has come to the forefront. Currently, few studies have examined the impact of personal and organizational factors of geriatric nursing assistants on elder neglect. From the perspective of geriatric nursing assistants, this study aims to explore the current situation and influencing factors of elder neglect in Chinese nursing homes. Methods A convenience sampling method was used to recruit 412 geriatric nursing assistants from 50 nursing homes in China. Participants were surveyed using a demographic questionnaire, the Elder Neglect Scale for Geriatric Nursing Assistants, the General Self-Efficacy Scale (GSES), and the Proactive Personality Scale (PPS). Spearman correlation analysis and multiple linear regression were used to analyze the factors influencing elder neglect. Results Geriatric nursing assistants scored a median of 74 out of 85 on the Elder Neglect Scale. Multiple linear regression analyses showed that the main personal factors influencing geriatric nursing assistants’ elder neglect were general self-efficacy (β = 0.312), proactive personality (β = 0.180), and advanced qualification (β = 0.084), while the main organizational factors included monthly salary ≤ 1,900 RMB (β = −0.256), no regular training after induction (β = −0.253), and the number of days off per month (3–4 days off β = 0.192, ≥ 5 days off β = 0.101). Conclusion Although geriatric nursing assistants are at low levels of elder neglect, it remains a cause for concern. Among the personal factors, geriatric nursing assistants who possessed proactive personalities, high self-efficacy and advanced qualifications, exhibited low levels of elder neglect. Among the organizational factors, those who possessed a high number of days off per month portrayed low levels of elder neglect. Conversely, those who received low monthly salaries and no regular training after induction portrayed high levels of elder neglect. To reduce the risk of elder neglect, nursing homes should give due consideration to candidates’ self-efficacy and proactive personality traits when recruiting, and focus on fostering these personality traits in their employees during their work. In addition, strengthening regular training for geriatric nursing assistants, optimizing the salary structure, and arranging rest days in a reasonable manner are also necessary measures.